1996
DOI: 10.1080/08927019609386273
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surfaces on sulphidogenic bacteria

Abstract: Sulphidogenic bacteria in oil reservoirs are of great economic importance in terms of souring, fouling and corrosion. Mixed cultures containing these bacteria were isolated from chalk formations in North Sea oil reservoirs. These were thermophilic cultures, growing optimally at 60°C. Oil formations are porous matrices, providing a very large surface area and ideal conditions for bacterial attachment, survival and growth. This study included assessments of sulphide production rates of thermophilic (t-)sulphidog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Another factor that has been observed to affect the growth and activity of SRB is the availability of suitable surfaces for bacterial attachment and colonization (e.g. Bass et al, 1996).…”
Section: Physiological Constraints On Sulfate-and Sulfur-reductionmentioning
confidence: 99%
“…Another factor that has been observed to affect the growth and activity of SRB is the availability of suitable surfaces for bacterial attachment and colonization (e.g. Bass et al, 1996).…”
Section: Physiological Constraints On Sulfate-and Sulfur-reductionmentioning
confidence: 99%
“…We demonstrated the ability of a sessile community of consortium EX251 attached to reservoir rock (chalk chips) to survive and recommence sulfide generation after 7 months of carbon source deprivation (Bass et al 1996). Walsh (1996) demonstrated that tSRB species are recoverable from open seawater.…”
Section: Discussionmentioning
confidence: 97%
“…The consortium was enriched and maintained in EX2 medium (Bass et al 1996). Seawater medium (SWM) was prepared by dissolving sodium pyruvate and Oxoid yeast extract (6.0 and 1.0 g L" 1 , respectively) in deaerated artificial seawater (ASW, prepared by dissolving 33.0 g Lr 1 Tropic Marin Aquarientechnik, Wartenburg, Germany in distilled water); pH was adjusted to 6.5.…”
Section: Culture Preparationmentioning
confidence: 99%
“…The novel opportunity of examining fresh hydrocarbon formation rock core from the UKCS has allowed the first report of the enrichment and initial characterisation of a thermophilic community of SRB. These subsurface environments are prone to bacterial growth and H 2 S production but until this study it was only possible to enrich for the causative SRB from produced waters [3, 14, 17]. It is extremely difficult to take geological specimens and make definitive statements concerning the presence of microorganisms on their surfaces [20].…”
Section: Discussionmentioning
confidence: 99%
“…Crushed inner core was inoculated into vials containing a pyruvate‐based SRB growth medium denoted EX2 [17]and a modification of Postgate's medium C [18]by the replacement lactate with pyruvate, denoted PCP. The medium was prepared anaerobically as described previously [17].…”
Section: Methodsmentioning
confidence: 99%